Improving The Understanding Of Riau Province Poltekkes Students' Understanding Of Health Legal Aspects: Pemahaman Mahasiswa Politeknik Kesehatan Kementerian Kesehatan Provinsi Riau Tentang Aspek Hukum Kesehatan - Ardiansah, Ardiansah; Eddy, Eddy Asnawi; Sudi, Sudi Fahmi (Universitas Lancang Kuning, 2024)
This community service activity was carried out by the Lancang Kuning University Postgraduate School Lecturer Team in the Riau Province Ministry of Health Polytechnic Meeting Room. The aim of this activity is for students to understand the legal aspects of health and understand the legal responsibilities of health workers in health services in hospitals. This community service uses lecture and interactive dialogue methods. In addition, participants filled out a pre-test questionnaire before the lecture and completed a post-test after the lecture. The results of this activity show that participants' understanding of legal counseling material has increased. The increase in participants' understanding was shown by the participants' answers, most of whom chose the correct answer regarding the 3 Main Actors, namely Hospitals, Health Workers and Patients who play a role in the hospital, Doctors/Health Personnel and Patients are legal subjects who have equal status, the rights of patients who has not been implemented, resulting in complaints due to complicated services, the Hospital can be sued if it does not provide good service, and the Hospital is responsible under administrative law for all losses arising from the negligence of health workers. Students from other universities need to receive knowledge regarding aspects of health law so they can understand the legal responsibilities of health workers in health services in hospitals.